Employment Growth Patterns in South Asia : Some Evidence from Interim Enterprise Survey Data - Friesenbichler, Klaus (2012)
This paper analyzes firm growth patterns in South Asia, using establishment level data from an Interim Enterprise Survey. The survey was conducted by the World Bank in 2009 and 2010 and covers seven countries in the region. The first finding suggests that size in the base year gains importance for employment growth and firm age is statistically insignificant for growth. This contradicts the thought that young and small firms are the bearers of growth. Second, establishments in larger localities expanded faster, confirming the observation of urban centers as growth poles. Third, establishments in areas of severe conflict performed worse than establishments in other areas. Interestingly, the distribution of growth rates shows that both firm growth and fast-growing firms exist in conflict regions.